EFL Undergraduate Students’ Expectations of Blended Learning in The Post-Pandemic - Ni Made Ari Dwipayanti; Made Hery Santosa; I Putu Indra Kusuma (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Education especially at the university level has experienced a shift from online learning during the COVID-19 pandemic to the post-pandemic era with blended learning. Blended learning combines learning using online learning methods combined with face-to-face learning. Students' experience of online learning during the pandemic sparked their hopes or expectations for the next learning they will do. Therefore, the role of teachers and educational institutions is important to know the needs of students to improve learning methods in the post-pandemic era by knowing students’ hopes or expectations. This study aimed to explore the students’ expectations for blended learning in the post-pandemic era. It employed a qualitative method by interviews and collected data from 10 7th-semester EFL university students in the year 2022/2023 in the public university in Bali. The interview guidelines were validated through face validity and content validity. The result revealed that the students preferred blended learning to be more interactive with lecturers and more access to resources, and technology to be used where necessary. The study provides valuable insights for the lecturers to enhance the teaching experience in future blended learning.